(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
Small business plays a crucial role in modern economic systems as a key driver of employment generation, innovation, competition, and inclusive economic growth. In both developed and developing economies, small business entities contribute significantly to GDP formation, diversification of production, and enhancement of social welfare. In recent years, the importance of small business investment activities has further increased due to globalization, technological transformation, and the transition toward sustainable and green economic development. However, despite its growing importance, financing small business investment activities remains one of the most challenging areas of economic policy and financial system development.